2012
DOI: 10.1016/j.jcf.2012.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory activity of vardenafil on induced lung inflammation in cystic fibrosis mice

Abstract: Vardenafil reduces lung inflammation with a more pronounced effect in F508del-CF mice, particularly on macrophage cell markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 32 publications
6
22
0
Order By: Relevance
“…Our data showed that LCA induced the activation of NF-κB and markedly increased the release of inflammatory cytokines, and these effects were greatly reduced by vardenafil treatment. These findings are consistent with previous investigations that showed the ability of vardenafil to suppress NF-κB activation and subsequently the release of inflammatory cytokines in autoimmune hepatitis [17] and lung inflammation [42].…”
Section: Discussionsupporting
confidence: 93%
“…Our data showed that LCA induced the activation of NF-κB and markedly increased the release of inflammatory cytokines, and these effects were greatly reduced by vardenafil treatment. These findings are consistent with previous investigations that showed the ability of vardenafil to suppress NF-κB activation and subsequently the release of inflammatory cytokines in autoimmune hepatitis [17] and lung inflammation [42].…”
Section: Discussionsupporting
confidence: 93%
“…More recently, we have found that vardenafil, selected as a representative PDE5 inhibitor for its longer-lasting CFTR activating effect, modulates the vicious circle of lung inflammation and attenuates the expression of pro-inflammatory cytokines and chemokines and cell infiltrates in the bronchoalveolar lavage (BAL) of CF and wild-type mice (Lubamba et al, 2012b). Intraperitoneal administration of a single pharmacological dose (0.14 mg/kg body weight) of vardenafil is followed by a reducing response in cell infiltrate and in the biosynthesis of several biomarkers of the inflammatory response.…”
Section: Pde5 Inhibitors For the Treatment Of Cystic Fibrosismentioning
confidence: 99%
“…injection, of a single therapeutic dose of vardenafil (vard) to wild-type (A) and F508del-CF (B) mice on the inflammatory response induced by lipopolyssaccharide from P. aeruginosa (LPS) . Biosynthesis of CCL-2 is significantly reduced in the bronchoalveolar lavage of vardenafil-treated CF and non-CF animals (Lubamba et al, 2012b). …”
Section: Pde5 Inhibitors For the Treatment Of Cystic Fibrosismentioning
confidence: 99%
“…PDEi are postulated to have anti-inflammatory effects resulting from their correction of chloride transport through the CFTR, or through the downstream effects of increased cyclic guanosine monophosphate on defective protein glycosylation and bacterial adherence; however, the exact mechanism of the anti-inflammatory activity of PDE is unknown. 11,14,16 …”
Section: Introductionmentioning
confidence: 99%
“…Recent in vitro and in vivo studies have shown that PDEi can potentiate CFTR-mediated chloride transport activity in respiratory and digestive tissues. 14,1720 Additionally, investigators have shown that this class of drugs corrects mislocalization of the mutant protein by displacing it from the intracellular compartment towards the apical cell compartment studied. 20,21 Thus, both the cellular localization and activity of F508del CFTR in the airway can be restored by PDEi.…”
Section: Introductionmentioning
confidence: 99%